An examination of age-related changes in the control of lexical and sublexical pathways in mapping spelling to sound. Issue 2 (3rd March 2016) - Cohen-Shikora, Emily R.; Balota, David A.
ABSTRACT: The current study investigated the extent to which young and older adults are able to direct attention to distinct processes in mapping spelling onto sound. Young and older adults completed either a speeded pronunciation task (reading aloud words) or regularization task (pronouncing words based on spelling-to-sound correspondences, e.g., pronouncing PINT such that it rhymes with HINT) in order to bias processing of lexical, whole-word information, or sublexical, spelling-to-sound mapping, respectively. Both younger and older adults produced reduced word-frequency effects and lexicality effects in the regularization task compared to the normal pronunciation task. Importantly, compared to younger adults, older adults produced exaggerated effects of task (i.e., pronunciation vs. regularization) on the observed frequency and lexicality effects. These results highlight both the flexibility of the lexical processing system and changes in the influence of the underlying lexical route due to additional 50 years of reading experience and/or changes in attentional control.